2012
DOI: 10.1111/j.1399-6576.2012.02660.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain in sedated and mechanically ventilated patients: an observational study

Abstract: Intratracheal suctioning evoked significant changes in some physiological and behavioral parameters. Some physiological changes were suppressed by analgesia, but at our ICU's standard doses, neither analgesia nor sedation attenuated changes in behavioral parameters at the intensity tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…The fact that BP does not have a significant increase can be attributed to compensatory mechanisms of the organism with the increase of HR at the painful procedure caused by decrease of peripheral vascular resistance, maintenance of systolic volume, etc. Similarly, Jeitziner found that the SBP increased during the painful procedure, which reinforces the idea that it is not just pain that causes change in hemodynamic parameters, but lots of factories can contribute with that event.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The fact that BP does not have a significant increase can be attributed to compensatory mechanisms of the organism with the increase of HR at the painful procedure caused by decrease of peripheral vascular resistance, maintenance of systolic volume, etc. Similarly, Jeitziner found that the SBP increased during the painful procedure, which reinforces the idea that it is not just pain that causes change in hemodynamic parameters, but lots of factories can contribute with that event.…”
Section: Discussionsupporting
confidence: 57%
“…Physiological values were recommended for assessing pain only as an aid, when the observation of behavioral indicators is not available, because it was concluded that in unconscious mechanically ventilated post cardiac surgery patients, an increase in MBP and HR occured both in painful and in nonpainful procedures . Correspondingly, other studies demonstrate inconsistency of this parameters for pain assessment, once they are kept stable, even during painful procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Pain evaluation was performed in conscious and unconscious patients before, during, and 20 min after nursing care [17, 18]. Inclusion criteria were (1) need of invasive mechanical ventilation and (2) admission in ICU longer than 24 h. Exclusion criteria were (1) age <18 years old, (2) infusion of neuromuscular blocking agents, (3) any diseases causing tetraplegic and paraplegic condition as well as lateral neurological signs, and (4) pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…In patients unable to communicate, electrophysiological measurements could allow for objective measurement of pain. The measurement of pupil size (pupillometry) appears to be more sensitive than behavioral parameters in a population of ICU patients undergoing nociceptive procedures [57]; whether pupillometry is useful compared with behavioral parameters during suctioning is less clear [58]. Which pain threshold should trigger analgesic administration is not well established.…”
Section: Reviewmentioning
confidence: 99%